The Evolution of Code-Switching in Multilingual Societies: A Sociolinguistic Perspective: https://doi.org/10.55966/assaj.2025.4.1.054 - Dr. Noor Jehan; Dr. Tabassum Javed; Shahida Banu (`, 2025)
This paper is a sociolinguistic study that examine the development of code-switching within multilingual communities with a special focus on the code-switching as a versatile communicative tool used in identity negotiation, social belonging, and cognitive versatility. Code-switching has previously been stigmatized but has recently become a normative technique especially among urban youth and digital natives who mix languages in an unobtrusive manner both offline and online. The study uses the qualitative research approaches such as discourse analysis and an ethnographic observation to analyze the code-switching patterns between generations, in educational environments, and digital environments such as social media. The results indicate that code-switching has multiple uses that range between the establishment of hybrid identities and solidarity and the facilitation of clear pedagogical communication and jokes. Digital worlds also enhance creative language blending, such as it is in memes, hashtags and polylingual online communication. The research questions monolingual tendencies in education and policymaking that should be replaced by inclusive strategies that support translanguaging as a form of cognitive and cultural resource. Keywords: Code-switching, Multilingualism, Sociolinguistics, Digital Communication, Hybrid Identity, Translanguaging, Language Policy, Social Media, Globalization, Educational Pedagogy